MENYIAPKAN MEDIA TUNGGAL UNTUK Drosophilla SECARA ALAMI - G Wayan Seregeg; Endang Susantini; Ita Ayu Rianawati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2001)
Preparing some media for Drosophilla in Indonesia both for research and education is still facing a big problem. Importing them from some advanced countries needs a big money, spare time, and great effort. Besides, the medium arrival in Indonesia is not always on time scheduled. Naturally, the food for Drosophilla is the fruits which have fragrant smell and sweet. The problem is that the fruit becomes damaged and covered with mold in a very short time, i.e. 5-7 days while the life cycle of Drosophilla takes 10-12 days. The natural media can be made durable if they are supplemented with some preservative. But, the new trouble arises, that is the lack of preventives availabilities. This study aims at preparing some single media naturally which are easily gained, cheap, natural (without preservative) but durable. The method of preparation is very simple. That is, take one ripe fruit, grinderred it, then put it into the bottle. That is meant by the natural single medium. The research result are as follows: (1) the pineapple (medium) lats 43-46 days; (2) black rise â€œtapeâ€? (fermented food) 31-33 days; (3) white rise â€œtapeâ€? 29-31 days; (4) white cassava â€œtapeâ€? 28-30 days and yellow cassava â€œtapeâ€? 20-25 days. It can be concluded that the pineapple medium and the naturally fermented media are durable.